Evaluation of an Outpatient Cervical Ripening Program Using Osmotic Dilators and Foley Balloon Catheters - Sidebottom, Abbey C.; Wunderlich, Whitney L.; Vacquier, Marc C.; Drake, Kelly A.; Goering, Mary P.; Hoffman, Sandra I.; Watson, David A.; Colicchia, Laura C. (American Journal of Perinatology, 2024)
This study aimed to describe patient characteristics, satisfaction, and outcome measures for patients undergoing outpatient cervical ripening.A retrospective cohort study using electronic health record data from March 2020 to March 2022 from a large health system. The sample included patients with a low-risk singleton pregnancy undergoing outpatient cervical ripening with either an osmotic dilator or Foley balloon catheter. A subset of patients completed satisfaction surveys. Frequencies and means were used to describe the population and conduct comparisons by device type. Inverse probability of treatment weighted estimates were generated to address baseline differences between patients in the two device groups.Outpatient cervical ripening was completed by 120 patients (80 osmotic dilators and 40 Foley balloon catheters). The mean time from insertion to inpatient admission was 16.2 ± 4.8 hours. The mean change in simplified Bishop score (SBS) was 1.8 ± 1.4 and the mean change in dilation was 1.8 ± 1.1 cm. There were no differences in the amount of cervical change by device type. Patients returned earlier than planned 16.7% of the time, primarily for contractions or rupture of membranes. Following outpatient cervical ripening, the time from admission to delivery was 19.9 ± 10.3 hours, with no difference by device type. Vaginal delivery occurred for 74.8% of patients. Patients reported overall satisfaction with the outpatient cervical ripening experience, with the highest satisfaction among those with osmotic dilators. Patients with both device types stated they would recommend outpatient cervical ripening to others, and experienced low levels of stress and discomfort at home prior to hospital admission.Patients participating in outpatient cervical ripening with osmotic dilators or Foley balloon catheters experienced clinically meaningful changes in dilation and SBSs while at home and reported general satisfaction with the outpatient program experience.
Keywords: cervical ripening; induction; Foley balloon; Dilapan-S; osmotic dilator; outpatient